(3ef ebGdI dLGdjfhS aj Cf bhi GdfaS JhGHY deRGL GdHOfs
(3ChdgG (B:s
(3bGd LGdjfhS deG aMUJ Yf CJHGY bhi GdfaS deRGL GdHOf eQGJ cKjQI eY eYdei hHEfaQGO ef faSi heY MPGb GdadGSaI hLOJ Gdbhd HPdc MbkG hfGaYkG ddOjf s
(3BNQgG (B:s
(3aEfg cGf ai GdUbGdjI adjSha hGMO hCeG ai CKjfI acKjQhf hcCf cKjQhf ai CbOjQ YOjei Gdage hCeG ai CKjfI aYdjdhf hGdeLO hGdTcQ ddg OGFekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs